Evaluation of the Success of Reclamation in the Waste Dump Area of ​​PT. J Resources, Bolaang Mongondow Regency, North Sulawesi Province - Mamonto, Siti Faisa; Supandi,; Shilvyanora Aprilia Rande, (ReTII, 2023)
J Resources Bolaang Mongondow is a gold mining company that has carried out reclamation activities, the implementation of reclamation which is carried out in a planned, systematic and sustainable manner is a form and effort to implement environmentally sound mining management. The purpose of this study was to determine the success rate of implementing land use, revegetation and final settlement based on Minister of Energy and Mineral Resources Decree No. 1827 and evaluate the implementation of revegetation in the waste dump area and optimize the success rate of reclamation. The method used in this study is a survey method in the form of field observations and measurements on various research study objects used to determine the suitability of reclamation implementation. From data processing carried out based on Minister of Energy and Mineral Resources Decree number 1827K/30/MEM/2018 in matrix 16 and matrix 17 using the Scoring Area method to find out the results of implementing reclamation activities. From the calculations that have been carried out, it is obtained that the success rate of reclamation of the waste dump area with an area of ​​4 ha is 88.7% (good) so that the implementation of the reclamation of the waste dump area of ​​PT. J Resources Bolaang Mongondow is acceptable.